CERITA RAKYAT LAKIPADADA: NEGOSIASI KEABADIAN DAN KENISBIAN DALAM PERSPEKTIF HEIDEGGER (Folkore of Lakipadada: Negotiations of Eternity and Relativity in Heidegger Perspective) - Eva Yenita Syam (SAWERIGADING, 2018)
This writing discusses of Torajan folkore“Lakipadada”which tells the story of someone who is looking for amulet of Tang Mate’eternity after witnessing all people he lovedpassed away. The theme is interesting due to contradictory to the law of nature regarding the changes in life. He makes various efforts to fight fate. Torajan know the principle of life for dying. All things are intended to celebrate a death by doing a ceremony that i sheld very luxury. In thiscontext, the folkore of Lakipadada presents as a story with different view of lifeand the collective memory of people. The data analysis using of Martin Heidegger perspective to understand negotiations of Torajan to wards the eternity and relativity. The result of the analysis has been carried out in finding negotiaton result in Lakipadada folkore, namely celebrating a dignified death. Keywords: negotiation; eternity; relativity; oral literature TorajaAbstrakTulisan ini membahas cerita rakyat Toraja “Lakipadada”yang bercerita tentang seseorang yang mencari azimat keabadian Tang Mate’ setelah menyaksikan semua orang yang disayanginya meninggal dunia. Tema ini menarik karena kontradiktif dengan hukum alam tentang perubahan pada kehidupan. Ia melakukan berbagai usaha melawan takdir. Masyarakat Toraja mengenal prinsip hidup untuk mati. Semua hal yang dilakukan dalam kehidupan ditujukan untuk merayakan kematian dengan upacara yang digelar sangat mewah. Dalam konteks ini, cerita Lakipadada hadir sebagai kisah yang berbeda dengan pandangan hidup dan ingatan kolektif masyarakatnya.Analisis data ini menggunakan perspektif Martin Heidegger untuk memahami negosiasi orang Toraja terhadap keabadian dan kenisbian. Hasil analisis yang telah dilakukan menemukan hasil negosiasi dalam cerita rakyat Lakipadada yaitu merayakan kematian yang bermartabat.